Performance Evaluation of Mannasim Framework for Wireless Sensor Network in Network Simulator 2 - Mohammed Ali, Mohammed Ali Amer (2012)
Optimizing sensor networks involves addressing a wide range of issues steaming from limited energy reserves, computation power, communication capabilities, and self-managing sensor nodes. The high cost and difficulties in deploying wireless sensor networks are the main challenges that motivate investigating the performance of a sensor network in a simulated environment. The Network Simulator 2 (ns-2) is one of the flexible tools available for network engineers to study how various protocols perform under different configurations and topologies. ns-2 lacks of modules for studying the sensor networks. However, many researchers have developed several modules for ns-2, which help exploring wireless sensor network before real deployment. This project concerns the reliability of Mannasim module for studying the performance of wireless sensor networks in ns-2. This project supports the analysis of different sensor network configurations under the demands of specific sensor applications. The project showed that Mannasim module reliable and it is able to meet the requirements of different layers that are involved in sensor networks.